Pemanfaatan Marketplace Shopee Untuk Menunjang Pemasaran Produk Madu Trigona di Desa Gisting Atas - Junaidah, Junaidah; Saputra, Rasyid; Fanisyah, Elsah (Communautaire: Journal of Community Service, 2022)
Community service By utilizing honey bee cultivation fromthe Trigona sp. species, honey bees are used as an additionalbusiness opportunity by utilizing the home page as a placefor honey bee cultivation, and there are not a few people whodeliberately use gardens as a place for cultivation. This isdone to improve the economy and welfare, especially forhoney bee farmers who are members of the "KelompokUsaha Perhutanan Sosial (KUPS)" as well as the communityand youth of residents around Gisting Atas Village, GistingDistrict, and Tanggamus Regency. This service is analyzedby the descriptive qualitative method, which is designed todescribe the entrepreneurial spirit. The method ofcommunity service in the study includes observation andquestion-and-answer interviews. The author deliversmaterial with coordination and communication, counselingand training, as well as socialization of science andtechnology training and the use of technology in makingbrands so that the brand can be patented and marketedwidely by utilizing technological advances through themarketplace and the public can find out how the process ofmaking a brand is, beginning with designing using theCanva application and ending with marketing using theShopee application.